2021
DOI: 10.3233/ica-200637
|View full text |Cite
|
Sign up to set email alerts
|

Human-robot interaction in Industry 4.0 based on an Internet of Things real-time gesture control system

Abstract: In the context of fast-growing digitization of industrial environments, Industry 4.0 aims to improve key elements to achieve more efficient processes, flexibility in customizing products and reduction in energy consumption, among other objectives. This paper presents a system that exploits the Internet of Things (IoT), massive data computation, and human-robot collaboration to reach these goals. The described system combines technological and human-centered aspects to enhance human-robot interaction. In fact, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Industry 4.0 [1] represents an innovative technological approach, where Cyber-Physical Systems [2], Artificial Intelligence [35,72], automatic decision systems [23], optimization solutions [18], exponential technologies [74], robotics [73] and circular business models are building the productive fabric [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Industry 4.0 [1] represents an innovative technological approach, where Cyber-Physical Systems [2], Artificial Intelligence [35,72], automatic decision systems [23], optimization solutions [18], exponential technologies [74], robotics [73] and circular business models are building the productive fabric [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Our recognition system, presented in [11] where further detail can be found, is composed of three main parts:…”
Section: Methodsmentioning
confidence: 99%
“…The component around which the experiments were built is our LoMoCA algorithm. It was developed to recognize movements using a small number of samples [11]. The algorithm will not be addressed in depth in this paper.…”
Section: Gesture Recognition Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent scientific discoveries and inventions have demonstrated that technology is also beginning to modify human capabilities, pushing them beyond their natural limits [2][3][4]. With the advance of technology, the interaction between humans and machines has been "improved", "augmented" or even "redesigned" [5][6][7][8]. This has made it not only interesting and intriguing but also viable and arising as a serious concept of scientific research and development [9,10].…”
Section: Introductionmentioning
confidence: 99%